2020
DOI: 10.1108/bpmj-07-2019-0279
|View full text |Cite
|
Sign up to set email alerts
|

Integrated approach for risk management in servitization decision-making process

Abstract: PurposeThe paper proposes an innovative systemic method helping decision-makers to control servitization transition process, through decision process risk diagnosis.Design/methodology/approachThe proposed method is based on the modeling of decision processes and risk identification and analysis. This method was based on an action-research approach, in close relationship with two companies (SMEs). The paper develops the feasibility experiment at Automelec company.FindingsThe method was successfully implemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
8
0
1
Order By: Relevance
“…The configuration of smart PSS networks during the design and engineering process is submitted to a high level of economic uncertainty and risks (Dahmani et al, 2020, Boucher et al, 2019. In fact, the association of smartness and service orientations opens a large potential of diversity in the way to configure the economic model of a smart PSS offer.…”
Section: Literature Review: Smart Pss Economic Assessmentmentioning
confidence: 99%
“…The configuration of smart PSS networks during the design and engineering process is submitted to a high level of economic uncertainty and risks (Dahmani et al, 2020, Boucher et al, 2019. In fact, the association of smartness and service orientations opens a large potential of diversity in the way to configure the economic model of a smart PSS offer.…”
Section: Literature Review: Smart Pss Economic Assessmentmentioning
confidence: 99%
“…How managers make decisions has become interesting topic for a few servitization scholars (see Cui et al, 2019;Dahmani et al, 2020;Huikkola et al, 2022;Kristensson & Magnusson, 2019). Huikkola et al, (2022) has found that in the era of digitalization and disruption, managers need to make decisions with autopilot, relying on mental shortcuts and "heuristics" that provide fast and frugal way to achieve "good enough" (see Gigerenzer, 2008) or better decisions (Bingham & Eisenhardt, 2014).…”
Section: Managerial Heuristicsmentioning
confidence: 99%
“…Managerial decision-making has recently gained interest among servitization scholars (Cui et al, 2019;Dahmani et al, 2020). When firms undergo strategic transitions such as (digital) servitization, managers need to pay special attention to making decisions in risky and complex settings.…”
Section: Managerial Decision-making Within the Strategic Transition Of The Firmmentioning
confidence: 99%
“…The existing literature on new service/solution development (NSD) has studied the evolution of processes (Panesar and Markeset, 2008), capabilities (Kindstr€ om et al, 2013), routines (Solem et al, 2021), innovation modes (Gremyr et al, 2014), and customer knowledge development (Johansson et al, 2019) among manufacturers engaged in servitization. Although there are studies investigating decision making in servitization (Cui et al, 2019;Dahmani et al, 2020) and NSD (see Kindstr€ om and Kowalkowski, 2009), little is yet known about managerial heuristics and, in particular, "simple rules" that guide how yes/no decisions are made in practice (Huikkola and Kohtam€ aki, 2021). Some previous studies have focused on a rational and slow decision-making approach among manufacturers engaged in servitization, but agile decision-making routines have not been given a particular emphasis (Kristensson and Magnusson, 2019).…”
Section: Introductionmentioning
confidence: 99%